2018
DOI: 10.1080/10810730.2018.1493061
|View full text |Cite
|
Sign up to set email alerts
|

The Perspective of HIV Providers in Western Kenya on Provider-Patient Relationships

Abstract: Enhancing effective adherence dialogue with HIV patients in an environment that promotes good provider-patient relationships, is key to optimizing the benefits of antiretroviral therapy (ART). The study examines the perspectives of HIV providers in western Kenya on provider-patient relationships. Sixty healthcare providers were sampled using convenience sampling methods from three Academic Model for Providing Access to Healthcare (AMPATH) sites (one urban and two rural). In-depth interviews conducted in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…25 In addition, we assessed the following domains: sociodemographic characteristics, knowledge about HIV and HIV treatment, and medication self-efficacy (HIV Self-Efficacy). 26 The selection of these constructs was informed by our previous qualitative work 7,27 and were considered potential confounders of the relationship between PPC skills and patient satisfaction with care. Socio-demographic characteristics included age in years, sex (male vs female), years in HIV care and disclosed HIV status to anyone (yes vs no).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…25 In addition, we assessed the following domains: sociodemographic characteristics, knowledge about HIV and HIV treatment, and medication self-efficacy (HIV Self-Efficacy). 26 The selection of these constructs was informed by our previous qualitative work 7,27 and were considered potential confounders of the relationship between PPC skills and patient satisfaction with care. Socio-demographic characteristics included age in years, sex (male vs female), years in HIV care and disclosed HIV status to anyone (yes vs no).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“… 26 A qualitative study conducted among HIV care providers in Kenya revealed that lack of adequate provider training and low system-level support were barriers to the adoption of patient-centered care. 29 Patients in this region may therefore be ready to communicate freely with their clinicians about the challenges they face with their care, and to partner with their clinicians to identify solutions. However, providers, and the health systems in general, may not yet be well prepared for this level of engagement from their patients, in part due to resource constraints.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Patients clearly perceived that poor adherence negatively influenced clinicians’ views of patients’ engagement with care. 29 Patients also clearly expressed the desire that clinicians provide higher quality interpersonal care, such as being more welcoming, concerned with patients’ social wellbeing, and empathetic when patients experienced challenges with care. Providers who have a higher respect for their patients tend to engage in more rapport-building, social chitchat, and positive talk with their patients, thus promoting more patient-centeredness.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Yet, low levels of HIV linkage, adherence, and retention in care persist in sub-Saharan Africa 1 due to a number of individual-level, social-level, and system-level barriers along the continuum of care. [3][4][5][6][7][8][9] In Kenya, system-level barriers such as poor provider-patient dynamics, lack of continuity in care, high patient burden, and long clinic hours, among others, have been well documented. [6][7][8][9] Effective and innovative system-level interventions that respond to the challenges patients' experience with HIV care are therefore urgently needed.…”
Section: Introductionmentioning
confidence: 99%